Application of Compost and Manure in the Biopore Infiltration Hole to Improve Saturated Hydraulic Conductivity (Shc) of Soil in the Coffee Root Zone - Lailatul Fitria; Kurniawan Sigit Wicaksono; Soemarno Soemarno (Jurnal Ilmu Lingkungan, 2024)
Coffee is one of the primary sources of foreign exchange in Indonesia. The factors causing fluctuations in coffee production are climate change, high soil density, less organic material, which causes coffee roots to be unable to absorb water and nutrients optimally. The soil water movement measured by saturated hydraulic conductivity which represents the soil ability to transmit water. The application of compost and manure in the biopore infiltration hole (BIH) is an effective technology in reducing surface-runoff and organic wastes management, as well as soil characteristics improvement. This study was conducted using a Randomized Block Design with four treatments and four replications. The treatments were P1 as control (without BIH), P2 (BIH without compost), P3 (BIH+compost), and P4 (BIH+goat manure). Data analysis was carried out using the Ftest (ANOVA), and continued with Least Significant Difference (LSD) test at 5% level, when there was a significant difference. Observations of soil characteristics were carried out every two months in three depth of root zone, 0-20 cm, 20-40 cm, and 40-60 cm. While the observation of the Auger hole at a depth of 0-30 cm and 0-60 cm. Research variables include soil texture, soil bulk density, Saturated Hydraulic Conductivity of soil by Auger-Hole, Soil Organic Matter (SOC), pH, Cation Exchange Capasity (CEC), and coffee yield. Results showed that treatment of BIH+goat manure gave the best results, measured by improving soil hydraulic conductivity up to 40%. The highest coffee yield was found in the BIH+manure treatment to 3.29 t ha-1.